Future cities and environmental sustainability. Issue 1 (25th February 2016) - Riffat, Saffa; Powell, Richard; Aydin, Devrim
Abstract: Massive growth is threatening the sustainability of cities and the quality of city life. Mass urbanisation can lead to social instability, undermining the capacity of cities to be environmentally sustainable and economically successful. A new model of sustainability is needed, including greater incentives to save energy, reduce consumption and protect the environment while also increasing levels of citizen wellbeing. Cities of the future should be a socially diverse environment where economic and social activities overlap and where communities are focused around neighbourhoods. They must be developed or adapted to enable their citizens to be socioeconomically creative and productive. Recent developments provide hope that such challenges can be tackled. This review describes the exciting innovations already being introduced in cities as well as those which could become reality in the near future.